Effects of disease control on productivity of village goats in southwest Nigeria - Opasina, B.A. (1985)
Peste des pattits ruminants (PPR) and manage have been associated with high mortality and morbidity among village goats in southwest Nigeria. Twelve months of PPR control for village goats resulted in 75% reductions in mortality among the groups vaccinated. Survival indices of kids at preweaning had no direct effect on mortality.